PENGARUH EDUKASI TERHADAP PENGETAHUAN MASYARAKAT DALAM MENYIMPAN DAN MEMBUANG OBAT DI RUMAH TANGGA - Hastuti, Sri; Rahem, Abdul; Hermansyah, Andi (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Improper storage and disposal of medicines at households is a public health issue which may lead to poor quality of medicines, damage the medicines, misuse of medicines and environmental pollution. Proper storage and disposal are influenced by the knowledge, attitudes and practices of the general public. This research aims to determine the effect of education on people’s knowledge in storing and disposing of medicines in Tambakrejo, Sidoarjo, Indonesia. A one group pretest - posttest design was conducted involving 120 housewife as respondents in Tambakrejo, Sidoarjo, Indonesia. The respondent was recruited using purposive sampling. A questionnaire was used to measure knowledge level before and after the intervention. The intervention was in the form of community counseling and leaflet distribution. Data were subsequently analyzed using Wilcoxon Signed Ranks Test. Of 120 respondents, the majority was older than 45 years (60.80%), unemployed (72.50%), stored up to 5 medicines at home (75.80%) and obtained medicines from community pharmacy (78.30%). There was an increase in the knowledge level before and after the intervention, from the average score of 44.4 to 70.8. Community education can increase people’s knowledge in storing and disposing of medicines.